Interface characteristics and mechanical behavior of aluminum alloy/ ultrahigh-strength steel plasma arc welded joint - Di Wu; Xiaolong Cai; Hongmei Li; Xiaoqi Zhang; Daqian Sun (Journal of Materials Research and Technology)
5A06 aluminum alloy and DP1180 ultrahigh-strength steel dissimilar metals were joined by plasma arc welding with AlCu6 welding wire. The interface of AlCu6 weld/steel joint was characterized by SEM, electron backscatter diffraction (EBSD) and focused ion beam-transmission electron microscopy (FIB-TEM). The results revealed that Fe–Al intermetallic compounds (IMCs) layer with double structure was formed at AlCu6 weld/steel interface, which were Fe4Al13 layer with needle-like shape and Fe2Al5 layer with tongue-shape. Fe2Al5 grains exhibited a clear preferential orientation in the [001] crystal direction and a strong silk texture in the <001> direction, but were weaker in Fe4Al13 grains. The average Schmidt factor of the Fe4Al13 and Fe2Al5 grains in the interface zone was 0.269 and 0.287, respectively, corresponding to the high brittleness and hardness of Fe4Al13 and Fe2Al5. The maximum tensile strength of the joints was 118.0 MPa and the aluminum/steel joints all fractured at the interface zones. The brittle IMCs of Fe4Al13 and Fe2Al5 played a crucial role in contributing to the joint fracture.